Fundamental Drivers of House Prices in Advanced Economies - Geng, Nan (IMF Working Papers; Working Paper ;, 2018)
House prices in many advanced economies have risen substantially in recent decades. But experience indicates that housing prices can diverge from their long-run equilibrium or sustainable levels, potentially followed by adjustments that impact macroeconomic and financial stability. Therefore there is a need to monitor house prices and assess whether they are sustainable. This paper focuses on fundamentals expected to drive long run trends in house prices, including institutional and structural factors. The scale of potential valuation gaps is gauged on the basis of a cross-country panel analysis of house prices in 20 OECD countries.